2021
DOI: 10.1007/s11469-021-00619-7
|View full text |Cite
|
Sign up to set email alerts
|

Facebook Addiction Partially Mediated the Association Between Stress Symptoms and Sleep Disturbance Among Facebook Users

Abstract: Stress symptoms, Facebook addiction, and sleep disturbances have important effects on the health of every individual. However, very few studies have examined the association between stress symptoms, Facebook addiction, and sleep disturbances. This study investigated the mediating effect of Facebook addiction on the association between stress symptoms and sleep disturbances among Facebook users in Vietnam. Three hundred fifty-four Facebook users in Vietnam have completed measures to assess symptoms of stress, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Because it is more about their feelings about lack of control and unpredictability than actual stressors, the current prevalence of perceived stress may be higher than actual stress. This study found that Facebook users who experienced moderate to high levels of stress are about four to six times more likely to develop Facebook addictions, which is consistent with earlier findings [17,20].…”
Section: Plos Global Public Healthsupporting
confidence: 92%
See 1 more Smart Citation
“…Because it is more about their feelings about lack of control and unpredictability than actual stressors, the current prevalence of perceived stress may be higher than actual stress. This study found that Facebook users who experienced moderate to high levels of stress are about four to six times more likely to develop Facebook addictions, which is consistent with earlier findings [17,20].…”
Section: Plos Global Public Healthsupporting
confidence: 92%
“…Therefore, it is reasonable to assume that depression symptoms moderate the relationship between daily stress and FA based on prior research [19]. Although the study in Vietnam showed that stressed people are more likely to be addicted to Facebook, which increases the risk of sleep disturbances [20].…”
Section: Introductionmentioning
confidence: 99%
“…Daily Facebook use (Brailovskaia et al, 2019b), duration of daily Facebook use (Brailovskaia et al, 2019a), Facebook addiction (Koc and Gulyagci, 2013;Atroszko et al, 2018;Brailovskaia et al, 2019b;Wang et al, 2021;Ho, 2021a,b;Ho et al, 2021b), Facebook dependence (Wolniczak et al, 2013), Facebook intrusion (Błachnio et al, 2021;Przepiórka and Błachnio, 2020), general Facebook use (Brailovskaia et al, 2019a), problematic Facebook use (Ho et al, 2021a), and time spent on Facebook (Hosen et al, 2021;Rahman and Zakaria, 2021) Positive Effects N/A No Effects Academic motive for using Facebook (Koc and Gulyagci, 2013), daily Facebook use (Brailovskaia et al, 2019b), daily informational motive for using Facebook (Koc and Gulyagci, 2013), Facebook addiction (Brailovskaia et al, 2019b), social motive for using Facebook (Koc and Gulyagci, 2013), and weekly time commitment on Facebook (Koc and Gulyagci, 2013) Example Facebook intrusion has been linked to the negative psychological effects of Facebook use associated with perceived insomnia (Błachnio et al, 2021). Excessive cognitive use of Facebook (Luqman et al, 2017), excessive hedonic use of Facebook (Luqman et al, 2017), excessive social use of Facebook (Luqman et al, 2017), Facebook addiction (Brailovskaia and Margraf, 2017;Atroszko et al, 2018Atroszko et al, , 2022Brailovskaia et al, 2018aBrailovskaia et al, ,b, 2019cÇakıcı et al, 2020;Eşkisu et al, 2020;Verseillié et al, 2021;Ho, 2021b;Balcerow...…”
Section: Effectsmentioning
confidence: 99%
“…Facebook addiction was significantly positively associated with perceived poorer sleep quality (Wang et al, 2021;Ho, 2021a;Ho et al, 2021a), perceived insomnia (Koc and Gulyagci, 2013;Brailovskaia et al, 2019a), and perceived sleep disturbance (Ho, 2021b). Furthermore, research showed that problematic Facebook use was significantly positively correlated with perceived poorer sleep quality (Ho et al, 2021a).…”
Section: Perceived Insomniamentioning
confidence: 99%
“…Some studies have revealed that addiction to social media platforms like Facebook is related to sleep problems and discomfort [ 25 ]. In fact, a study concluded that people who tend to be addicted to Facebook are at a higher risk of experiencing sleep disorders [ 26 , 27 ]. Some factors such as physical inactivity, deficit of skills, depression or anxiety, could increase the risk of presenting these problems [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%